Long-term survival without surgery in NSCLC patients with synchronous brain oligometastasis: systemic chemotherapy revisited - Sato, Jun (J Thorac Dis, 2018)
BACKGROUND: Among patients with metastatic non-small-cell lung cancer (NSCLC), patients with TNM stage N0 to N1 and brain oligometastases (BOM) (less than 5 metastases) as the sole distant lesion (N0–1 BOM) who receive surgical treatments for the primary and metastatic sites reportedly have a better prognosis. Little data is available regarding the outcomes of patients treated with only systemic chemotherapy for the primary site and definitive treatment for synchronous BOM, compared with the outcomes of patients receiving surgical treatment for the primary site. METHODS: Stage IV NSCLC patients with or without N0–1 BOM, who underwent chemotherapy for the primary site between January 2000 and December 2010 were identified from the records of our institution. RESULTS: Among 936 advanced NSCLC patients treated with systemic chemotherapy, 19 patients had N0–1 BOM at presentation. The median overall survival (OS) period of the N0–1 BOM patients was 16.0 months (95% CI, 11.8–20.2 months), while that of the N2–3 BOM + non-BOM patients was 14.5 months (95% CI, 13.2–15.8 months), compared with 7–9 months in previous reports. The median 3- and 5-year survival rates of the N0–1 BOM patients were 28% and 19%. CONCLUSIONS: The treatment outcomes of the N0–1 BOM patients who did not receive surgery for the primary site were better than those of the N2–3 BOM + non-BOM patients. A randomized trial evaluating the efficacy of surgery for the primary site in N0–1 BOM patients is warranted.